2004
DOI: 10.1038/sj.onc.1207582
|View full text |Cite
|
Sign up to set email alerts
|

Induction of hTERT expression and phosphorylation by estrogen via Akt cascade in human ovarian cancer cell lines

Abstract: We examined the mechanism by which estrogen regulates telomerase activity in Caov-3 human ovarian cancer cell lines, which express ER, to determine whether the regulation affects the expression and/or phosphorylation of the telomerase catalytic subunit (hTERT). 17b-Estradiol (E 2 ) induced telomerase activity and hTERT expression. Transient expression assays using luciferase reporter plasmids containing various fragments of hTERT promoter showed that the estrogen-responsive element appeared to be partially res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
82
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(90 citation statements)
references
References 57 publications
7
82
0
Order By: Relevance
“…telomerase activity. It is shown that specific growth hormonereleasing hormone (GHRH) antagonists decrease telomerase activity in a glioblastoma cell line (34). It is of interest to note that the GHRH antagonist-mediated decrease in telomerase activity is also associated with down-regulation of hTERT mRNA and without change in the level of hTR or TP1 mRNA as is observed with autocrine hGH in this study.…”
Section: Discussionmentioning
confidence: 58%
“…telomerase activity. It is shown that specific growth hormonereleasing hormone (GHRH) antagonists decrease telomerase activity in a glioblastoma cell line (34). It is of interest to note that the GHRH antagonist-mediated decrease in telomerase activity is also associated with down-regulation of hTERT mRNA and without change in the level of hTR or TP1 mRNA as is observed with autocrine hGH in this study.…”
Section: Discussionmentioning
confidence: 58%
“…At post-translational levels, we and others have shown that hTERT is a phosphoprotein and that phosphorylation by protein kinase C and Akt up-regulates telomerase activity [61][62][63]. Conversely, protein phosphatase 2A dephosphorylates hTERT and inhibits telomerase activity [61].…”
Section: Molecular Mechanisms Regulating Telomerase Activitymentioning
confidence: 92%
“…Data from studies on hTERT derived peptides and on ovarian cancer cell lines have suggested that PKB/Akt induced phosphorylation of hTERT can upregulate telomerase activity. 25,36 The DJ-1 related regulation of PKB/Akt phosphorylation status can thus have dual consequences for hTERT, at the transcriptional and posttranscriptional level, with additive effects regarding telomerase activity. The siRNA experiments also verified that DJ-1 can influence the telomerase activity level.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 PKB/Akt can also affect telomerase expression through post-transcriptional phosphorylation of the hTERT protein as indicated in studies on myeloma and ovarian cancer cells. 24,25 Thus, the PI-3-kinase-PKB/Akt pathway can interact with hTERT and telomerase expression at both the transcriptional and posttranscriptional level and since DJ-1 might be a potentially important regulator of this pathway the present study was undertaken to further investigate this issue in RCC. We demonstrate here an association among DJ-1, cMyc and hTERT gene expression levels in a large series of ccRCC indicating a putative signaling pathway in this tumor type.…”
mentioning
confidence: 99%